Silicon nitride films deposited with an electron beam created plasma - Collins, G. J., author; Zarnani, H., author; Thompson, L. R., author; Rocca, Jorge J., author; Emery, K. A., author; Bishop, D. C., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1984)
Silicon nitride films have been deposited using an electron beam created plasma in a silane, ammonia, and nitrogen mixture. The films were deposited at substrate temperatures between 50 and 400 °C. Physical, chemical, and electrical properties of these films are reported.